Facilitating enzymatic hydrolysis with a novel guaiacol-based deep eutectic solvent pretreatment. (April 2021) - Huang, Chen; Zhan, Yunni; Cheng, Jinyuan; Wang, Jia; Meng, Xianzhi; Zhou, Xuelian; Fang, Guigan; Ragauskas, Arthur J.
Highlights: A novel guaiacol-based DES pretreatment was established in this study. Trace AlCl3 addition improved the efficiency of the guaiacol-DES pretreatment. The pretreatment facilitated the enzymatic hydrolysis of WS, bamboo and poplar. Abstract: Herein, we established a novel deep eutectic solvent (DES) using lignin-derived guaiacol as hydrogen bond donor (HBD). The sole ChCl/guaiacol system was found to be inefficient for the fractionation of wheat straw (WS), while the incorporation of trace AlCl3 significantly facilitated the degradation of hemicellulose and lignin, resulting in a complete enzymatic digestibility of the pretreated WS. Further, this study revealed that the DES-degraded lignin was readily precipitated during the washing process, and thus hindered the enzymatic hydrolysis of poplar and bamboo (with hydrolysis yield of 42.03% and 71.67%, respectively). Alkali washing offers a possible approach to remove the precipitated lignin, after which a near 100% hydrolysis yield was also obtained for poplar and bamboo.